Strategi Guru Akidah Akhlak dalam Membentuk Akhlak Mulia pada Siswa di MTs Muhammadiyah 15 Medan - Ahmad Syafii MRP (STID Raudlatul Iman Sumenep, 2024)
Teacher strategy is a general approach to teaching that applies to a variety of subjects and is used to meet a variety of learning objectives in schools. Therefore, a series of teacher strategies must contain material content that is based on the principle of changing student character values. This research has a background that morals teachers have an important role in shaping the noble character of students. As an educator, a teacher of aqidah morals is responsible for helping students understand good moral and ethical values. The research location is at MTs Muhammadiyah 15 medan. In this research, the researcher uses a case study research type with a qualitative approach that is descriptive in nature and produces effective data from information sources. The researcher concluded that in forming noble character in student teachers have the planning, implementation and implementation results that have been carried out in Madrasas. There are results from the observations that the researchers made, in the Teacher Planning Akidah Akhlak in forming noble character in students at MTs Muhammadiyah 15 medan. namely the teacher has prepared a written plan and an unwritten plan. The implementation of the teacher's Aqidah Akhlak in forming noble character in MTs Muhammadiyah 15 medan. students in the teacher's lesson plan is divided into three stages, namely preliminary activities, core activities, and closing activities. In conveying learning material, teachers use various methods and media related to the formation of noble character in students. The results of implementing the Teacher's Akidah Akhlak plan in forming noble character in students at MTs Muhammadiyah 15 medan. are that students become more religious and there is a change in behavior for the better and are able to apply noble character in everyday life.